Una & Miguel - Bose, Lilledeshan; Sinaban, Borg; Bose, Lilledeshan; Quibilan, Sunantha Mendoza (Quezon City Adarna House, Inc., 2002)
For these two, love is truly a long shot. But when they're forced to work together as punishment for a prank-gone-wrong, they find that falling in love might not be so impossible after all. Will opposites attract? Or will they repel?.
Also includes the story, Lia and Camille, by Lilledeshan Bose and Sunantha Medoza-Quibilan.
Keywords: Love stories, Philippine (English); Philippine fiction (English)